Preparation method of high-humidity-resistant wood-based friction nano-generator
Through dopamine hydrochloride modification and carbon nanotube loading technology, combined with compression and carbonization treatment, the conductivity and moisture resistance of natural wood in friction nanogenerators are solved, and the preparation of high-efficiency wood-based friction nanogenerators is achieved to ensure that Work well in high humidity environments and improves its environmental friendliness.
Patent Information
- Application Number
- CN202411408540.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The friction materials and electrode materials of traditional friction nanogenerators are not renewable and have poor environmental friendliness. Due to the anisotropy, poor conductivity and insufficient friction polarity, natural wood is difficult to directly apply to friction nanogenerators. At the same time, the modification treatment causes harm to the environment. And the performance is susceptible to humidity.
Modified wood with dopamine hydrochloride and loaded with carbon nanotubes on its surface. The conductivity of the wood is significantly improved through electrostatic adsorption, and the conductivity and moisture resistance of the wood are improved through compression and carbonization, and a high humidity-resistant wood-based friction is prepared. Nano generator.
It significantly improves the output performance of wood-based friction nanogenerators, ensures normal operation in high humidity environments, and has good biocompatible modifiers, and is suitable for wood with different sections, enhancing its application potential as a triboelectric material.
Smart Images

Figure CN119298710A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a friction nanogenerator. Background Art
[0002] Based on the working principle of triboelectric effect and electrostatic induction, friction nanogenerators can directly convert waste mechanical energy into electrical energy, thereby realizing the reuse of waste energy. However, the friction materials and electrode materials of traditional friction nanogenerators are usually composed of non-renewable polymers and metal materials. These materials are difficult to recycle and non-degradable, making them unsuitable for large-scale applications.
[0003] As one of the most abundant natural biomaterials on earth, wood has the characteristics of sustainability, renewability, good environmental properties and biodegradability, and has attracted extensive attention from researchers in recent years. However, natural wood also has disadvantages such as anisotropy and poor conductivity, and its triboelectric effect is extremely poor, almost in the middle of the triboelectric series, that is, close to electrical neutrality, which limits its direct application as a friction material in triboelectric nanogenerators.
[0004] At present, there have been many studies on using wood as a friction material for triboelectric nanogenerators. The friction polarity of wood can be effectively improved by modifying the wood, such as chemical treatment, plasma etching, and hot pressing. However, some highly polar functional groups introduced during the modification process will cause harm to the environment and have extremely poor biocompatibility. At the same time, the hygroscopic properties of wood make it affected by high humidity environments during application, which greatly limits the widespread application of wood-based triboelectric nanogenerators. Summary of the invention
[0005] The present invention aims to solve the problems that existing natural wood has anisotropy, poor conductivity, and poor friction polarity, and cannot be directly applied to friction nanogenerators; to solve the problems that the modification treatment used for existing wood as friction material causes harm to the environment and has extremely poor biocompatibility, and the output performance of wood-based friction nanogenerators is easily affected by high humidity, and thus provide a method for preparing a high-humidity resistant wood-based friction nanogenerator.
[0006] A method for preparing a high-humidity resistant wood-based friction nanogenerator is carried out according to the following steps:
[0007] 1. Preparation of friction materials:
[0008] ① Dissolve dopamine hydrochloride in Tris solution and disperse evenly to obtain a modified solution;
[0009] ② Immersing the delignified wood in a modification solution and then drying it to obtain polydopamine-modified wood;
[0010] ③ Place the polydopamine-modified wood in the carbon nanotube dispersion, apply vacuum pressure until the wood is completely immersed and maintained, then dry, repeat the immersion and drying multiple times until the wood turns black, and obtain the carbon nanotube-loaded wood;
[0011] ④ compressing the carbon nanotube-loaded wood to obtain compressed carbon nanotube-modified wood;
[0012] 2. Preparation of electrode materials:
[0013] The natural wood chips are compressed to obtain veneers, and then the veneers are carbonized to obtain carbonized wood veneers;
[0014] 3. Assembly of wood-based friction nanogenerator:
[0015] ① Using compressed carbon nanotube-modified wood as the positive friction material and carbonized wood veneer as the positive electrode material, and then assembling them to obtain the positive electrode material of the friction nanogenerator;
[0016] ② Using polytetrafluoroethylene film as negative friction material and copper foil as negative electrode material, and then assembling them to obtain the negative electrode material of the friction nanogenerator;
[0017] ③ Assemble the positive electrode material of the friction nanogenerator and the negative electrode material of the friction nanogenerator to obtain a high-humidity resistant wood-based friction nanogenerator.
[0018] The beneficial effects of the present invention are:
[0019] 1. The modifier of the present invention is dopamine hydrochloride, which has good biocompatibility and is green and environmentally friendly;
[0020] 2. Natural wood has poor friction polarity and cannot be directly used as a triboelectric material. The present invention modifies the wood with polydopamine and loads rich amino groups on its surface, which significantly enhances its positive friction polarity and enables it to be used as a positive triboelectric material.
[0021] 3. There is a lack of adhesion between wood and carbon nanotubes. The present invention first loads polydopamine on the surface and pores of wood, and then polydopamine allows carbon nanotubes to be evenly loaded on the surface and pores of wood through electrostatic adsorption. At the same time, the addition of carbon nanotubes significantly improves the conductivity of wood, thereby increasing the output performance of wood-based friction nanogenerators;
[0022] 4. The present invention uses the same modification method to modify the cross section, radial section and tangential section of wood, respectively, and verifies that the modification method is applicable to all sections of wood;
[0023] 5. The present invention makes the microstructure of the wood chips denser and thinner by simply compressing and carbonizing the wood chips, which is conducive to the rapid transmission of electrons and makes them have good conductivity and high moisture resistance;
[0024] 6. The wood-based friction nanogenerator prepared by the present invention can maintain good output performance under different humidity environments and can work normally under a high humidity environment of 80%.
[0025] Instruction Manual
[0026] Figure 1 The structural diagram and working principle diagram of the high-humidity-resistant wood-based friction nanogenerator prepared in Example 1;
[0027] Figure 2 This is a SEM image of the compressed carbon nanotube-modified wood prepared in step 1④ of Example 1;
[0028] Figure 3 This is a SEM image of the natural wood chips described in step 2 of Example 1 and the carbonized wood veneer prepared in step 2;.
[0029] Figure 4 This is a graph showing the output performance of the high-humidity-resistant wood-based friction nanogenerator prepared in Example 1 under different ambient humidity conditions;
[0030] Figure 5 This is a graph showing the output performance of the wood-based friction nanogenerator prepared in Comparative Example 1 under different ambient humidity conditions;
[0031] Figure 6 Output performance diagram of wood-based friction nanogenerators prepared in Comparative Examples 1 to 4;
[0032] Figure 7 The ultra-depth-of-field microscope images of the carbon nanotube-loaded wood prepared in step 1③ of Example 1 and the compressed carbon nanotube-modified wood prepared in step 1④;
[0033] Figure 8 The physical pictures are of the carbon nanotube-loaded wood prepared in step 1③ of Example 1 and the compressed carbon nanotube-modified wood prepared in step 1④;
[0034] Fig. 9 The SEM images of the compressed carbon nanotube-modified wood prepared in step 1④ of Example 1 and Comparative Examples 5 and 6;
[0035] Fig.10 The output performance diagram of the friction nanogenerator prepared with wood of different cross sections in Comparative Examples 1, 5 and 6. DETAILED DESCRIPTION
[0036] Specific implementation method 1: This implementation method is a method for preparing a high-humidity resistant wood-based friction nanogenerator, which is carried out according to the following steps:
[0037] 1. Preparation of friction materials:
[0038] ① Dissolve dopamine hydrochloride in Tris solution and disperse evenly to obtain a modified solution;
[0039] ② Immersing the delignified wood in a modification solution and then drying it to obtain polydopamine-modified wood;
[0040] ③ Place the polydopamine-modified wood in the carbon nanotube dispersion, apply vacuum pressure until the wood is completely immersed and maintained, then dry, repeat the immersion and drying multiple times until the wood turns black, and obtain the carbon nanotube-loaded wood;
[0041] ④ compressing the carbon nanotube-loaded wood to obtain compressed carbon nanotube-modified wood;
[0042] 2. Preparation of electrode materials:
[0043] The natural wood chips are compressed to obtain veneers, and then the veneers are carbonized to obtain carbonized wood veneers;
[0044] 3. Assembly of wood-based friction nanogenerator:
[0045] ① Using compressed carbon nanotube-modified wood as the positive friction material and carbonized wood veneer as the positive electrode material, and then assembling them to obtain the positive electrode material of the friction nanogenerator;
[0046] ② Using polytetrafluoroethylene film as negative friction material and copper foil as negative electrode material, and then assembling them to obtain the negative electrode material of the friction nanogenerator;
[0047] ③ Assemble the positive electrode material of the friction nanogenerator and the negative electrode material of the friction nanogenerator to obtain a high-humidity resistant wood-based friction nanogenerator.
[0048] The beneficial effects of this embodiment are:
[0049] 1. The modifier used in this embodiment is dopamine hydrochloride, which has good biocompatibility and is green and environmentally friendly;
[0050] 2. Natural wood has poor friction polarity and cannot be directly used as a triboelectric material. In this embodiment, the wood is modified with polydopamine to load rich amino groups on its surface, so that its positive friction polarity is significantly enhanced, and it can be used as a positive triboelectric material.
[0051] 3. There is a lack of adhesion between wood and carbon nanotubes. In this embodiment, polydopamine is first loaded on the surface and pores of wood, and then polydopamine is used to uniformly load carbon nanotubes on the surface and pores of wood through electrostatic adsorption. At the same time, the addition of carbon nanotubes significantly improves the conductivity of wood, thereby increasing the output performance of wood-based friction nanogenerators.
[0052] 4. This embodiment uses the same modification method to modify the wood on the cross section, radial section and tangential section respectively, verifying that the modification method is applicable to all sections of the wood;
[0053] 5. This embodiment makes the wood chips more compact and thinner in microstructure by simply compressing and carbonizing the wood chips, which is conducive to the rapid transmission of electrons and makes them have good conductivity and high moisture resistance;
[0054] 6. The wood-based friction nanogenerator prepared in this embodiment can maintain good output performance under different humidity environments and can work normally under a high humidity environment of 80%.
[0055] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the concentration of dopamine hydrochloride in the modified solution described in step 1① is 0.5mg / mL to 2mg / mL; the concentration of the Tris solution described in step 1① is 5mmol / L to 15mmol / L, and the pH is 8 to 8.5. Others are the same as specific embodiment 1.
[0056] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the delignified wood described in step 1② is specifically prepared according to the following steps: glacial acetic acid is added dropwise to a 1% to 3% by mass NaClO2 aqueous solution until the pH is 4 to 6 to obtain an impregnation solution, the wood is impregnated in the impregnation solution, and the temperature is kept at 80°C to 100°C for 8h to 24h, and the impregnation solution is replaced every 6h to 8h during the insulation process until the wood turns white, and then washed with deionized water, and finally freeze-dried at a temperature of -80°C to -60°C for 12h to 24h to obtain delignified wood. The rest is the same as specific implementation method one or two.
[0057] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the wood is a basswood slice with a cross section, radial section or tangential section, and has a thickness of 1 mm to 1.5 mm. Other aspects are the same as specific embodiments 1 to 3.
[0058] Specific embodiment 5: This embodiment differs from the specific embodiments 1 to 4 in that the volume ratio of the delignified wood to the modified liquid in step 1② is 1 cm 3: (100-300) mL; the volume ratio of the polydopamine-modified wood and the carbon nanotube dispersion described in step 1 ③ is 1 cm 3 : (100-300) mL. The rest is the same as the specific embodiments 1 to 4.
[0059] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the carbon nanotubes in the carbon nanotube dispersion described in step 1 ③ are hydroxylated multi-walled carbon nanotubes with a diameter of 5nm to 15nm and a length of 2μm to 8μm; the concentration of the carbon nanotube dispersion described in step 1 ③ is 0.5mg / mL to 2mg / mL. Others are the same as specific embodiments 1 to 5.
[0060] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that: in step 1②, the delignified wood is immersed in the modification liquid for 12h to 48h at room temperature; in step 1③, vacuum pressurization is applied until the wood is completely immersed and maintained for 12h to 48h at room temperature. Others are the same as Specific embodiments 1 to 6.
[0061] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the compression treatment described in step 1④ and step 2 is performed at room temperature and a pressure of 5MPa to 20MPa for 1h to 2h. The rest is the same as specific embodiments 1 to 7.
[0062] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the natural wood chips described in step 2 are natural basswood chips with a thickness of 0.5 mm to 1.5 mm. The rest is the same as specific embodiments 1 to 8.
[0063] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the carbonization treatment described in step 2 is specifically carried out in a nitrogen atmosphere at a heating rate of 2°C / min to 10°C / min to 700°C to 900°C, and then the carbonization treatment is carried out for 1h to 2h in a nitrogen atmosphere at a temperature of 700°C to 900°C. Other aspects are the same as specific embodiments 1 to 9.
[0064] The following examples are used to verify the beneficial effects of the present invention:
[0065] Embodiment 1:
[0066] A method for preparing a high-humidity resistant wood-based friction nanogenerator is carried out according to the following steps:
[0067] 1. Preparation of friction materials:
[0068] ① Dissolve dopamine hydrochloride in Tris solution and disperse evenly to obtain a modified solution;
[0069] The concentration of dopamine hydrochloride in the modified solution is 0.5 mg / mL; the concentration of the Tris solution is 10 mmol / L, and the pH is 8.5;
[0070] ② Under room temperature, the delignified wood is immersed in the modification liquid for 24 hours, and then dried to obtain the polydopamine-modified wood;
[0071] The volume ratio of the delignified wood to the modified liquid is 1 cm 3 :150mL;
[0072] ③ Place the polydopamine-modified wood in a carbon nanotube dispersion, apply vacuum pressure at room temperature until the wood is completely immersed and maintain for 24 hours, then dry, repeat the immersion and drying multiple times until the wood turns black, and obtain carbon nanotube-loaded wood;
[0073] The volume ratio of the polydopamine-modified wood to the carbon nanotube dispersion is 1 cm 3 : 150mL; the carbon nanotubes in the carbon nanotube dispersion are hydroxylated multi-walled carbon nanotubes with a diameter of 5nm to 15nm and a length of 2μm to 8μm; the concentration of the carbon nanotube dispersion is 1mg / mL;
[0074] ④ Under the conditions of room temperature and a pressure of 10 MPa, the carbon nanotube-loaded wood was compressed for 1 hour to obtain compressed carbon nanotube-modified wood;
[0075] 2. Preparation of electrode materials:
[0076] Under the conditions of room temperature and a pressure of 10 MPa, the natural wood chips were compressed for 1 hour to obtain a veneer, and the temperature was increased to 800°C at a rate of 5°C / min under a nitrogen atmosphere, and then the veneer was carbonized for 2 hours under the conditions of a nitrogen atmosphere and a temperature of 800°C to obtain a carbonized wood veneer;
[0077] The natural wood chips are natural basswood chips with a thickness of 0.5 mm;
[0078] 3. Assembly of wood-based friction nanogenerator:
[0079] ① Using compressed carbon nanotube-modified wood as the positive friction material and carbonized wood veneer as the positive electrode material, and then assembling them with conductive glue to obtain the positive electrode material of the friction nanogenerator;
[0080] ②Use polytetrafluoroethylene film as negative friction material and copper foil as negative electrode material, and then assemble them with conductive glue to obtain the negative electrode material of the friction nanogenerator;
[0081] ③ Assemble the positive electrode material of the friction nanogenerator with the negative electrode material of the friction nanogenerator to obtain a wood-based friction nanogenerator that is resistant to high humidity;
[0082] The delignified wood described in step 1② is specifically prepared according to the following steps: glacial acetic acid is added dropwise to a 3% by mass NaClO2 aqueous solution until the pH is 4.5 to obtain an impregnation solution, the wood is immersed in the impregnation solution, and the temperature is kept at 80°C for 12 hours, and the impregnation solution is replaced every 6 hours during the insulation process until the wood turns white, and then washed with deionized water, and finally freeze-dried at a temperature of -80°C for 24 hours to obtain delignified wood; the wood is a tangential section of basswood chips with a size of 1mm×30mm×30mm (radial×tangential×longitudinal), and is cleaned with ethanol.
[0083] Comparative Example 1: This comparative example is different from Example 1 in that the positive electrode material in step 3① is replaced with copper foil. The rest is the same as Example 1.
[0084] Comparative Example 2: This comparative example is different from Example 1 in that the positive friction material in step 3① is replaced by natural wood, and the positive electrode material is replaced by copper foil. The rest is the same as Example 1.
[0085] Comparative Example 3: This comparative example is different from Example 1 in that: Steps 1 ③ and ④ are omitted; the positive friction material in Step 3 ① is replaced by the polydopamine-modified wood prepared in Step 1 ②, and the positive electrode material is replaced by copper foil. The rest is the same as Example 1.
[0086] Comparative Example 4: This comparative example is different from Example 1 in that: Step 1④ is omitted; the positive friction material in Step 3① is replaced by the carbon nanotube-loaded wood prepared in Step 1③, and the positive electrode material is replaced by copper foil. The rest is the same as Example 1.
[0087] Comparative Example 5: This embodiment is different from the first embodiment in that the wood in step 1 ② is a cross-section of basswood with a size of 30 mm × 30 mm × 1 mm (radial × tangential × longitudinal); the positive electrode material in step 3 ① is replaced with copper foil. The rest is the same as the first embodiment.
[0088] Comparative Example 6: The difference between this embodiment and the first embodiment is that the wood in step 1② is radially sectioned basswood with a size of 30mm×1mm×30mm (radial×tangential×longitudinal); the positive electrode material in step 3① is replaced with copper foil. The rest is the same as the first embodiment.
[0089] Figure 1This is a structural schematic diagram and working principle diagram of the high-humidity resistant wood-based friction nanogenerator prepared in Example 1; it can be seen from the figure that when the two friction layers are in contact, due to different electron affinities, the surface of the polytetrafluoroethylene film is negatively charged, while the surface of the positive friction material is positively charged. When they begin to separate from each other, due to the electrostatic induction effect, electrons flow from the top electrode to the bottom electrode through the external circuit. When the two friction layers are completely separated, the transmitted electrons reach a saturated state. Similarly, when they come into contact again, electrons flow from the bottom electrode back to the top electrode, generating an opposite electrical signal.
[0090] Figure 2 This is the SEM image of the compressed carbon nanotube-modified wood prepared in step 1④ of Example 1; it can be seen from the figure that polydopamine and carbon nanotubes are evenly loaded on the surface and inside the pores of the wood, and the macropores of the sample are significantly reduced after compression treatment, and the coating composed of polydopamine and carbon nanotubes becomes smooth.
[0091] Figure 3 This is an SEM image of the natural wood chips described in step 2 of Example 1 and the carbonized wood veneer prepared in step 2; it can be seen from the figure that after the wood chips are simply compressed and carbonized, the microstructure of the wood chips is denser and the thickness is thinner, which is conducive to the rapid transmission of electrons.
[0092] Under different humidity environmental conditions, the high-humidity resistant wood-based friction nanogenerator prepared in Example 1 and the wood-based friction nanogenerator prepared in Comparative Example 1 were subjected to contact separation power generation tests, with a pressure of 100N and a frequency of 1Hz. Figure 4 This is the output performance diagram of the high-humidity-resistant wood-based friction nanogenerator prepared in Example 1 under different ambient humidity; it can be seen from the figure that as the humidity increases from 20% to 80%, the open circuit voltage drops from 82.2V to 50.85V, and the short circuit current drops from 0.95μA to 0.72μA, which are only dropped by 38.14% and 24.21% respectively. Figure 5 The output performance diagram of the wood-based friction nanogenerator prepared in comparative example 1 under different environmental humidity; it can be seen from the figure that as the humidity increases from 20% to 80%, the open circuit voltage decreases from 98.12V to 42.04V, and the short circuit current decreases from 1.1μA to 0.55μA, with a decrease of 57.15% and 50%, respectively; Figure 4 and Figure 5 It can be seen that the carbonized wood veneer prepared in step 2 of Example 1 can completely replace copper foil as an electrode material for use in friction nanogenerators, and the output performance of the friction nanogenerator prepared with the carbonized wood veneer as the electrode material in a high humidity environment is even better than that of the friction nanogenerator with copper foil as the electrode.
[0093] Under the condition of a humidity environment of 20% RH, the wood-based friction nanogenerators prepared in Comparative Examples 1 to 4 were subjected to contact separation power generation tests with a pressure of 100 N and a frequency of 1 Hz. Figure 6 The output performance diagram of the wood-based friction nanogenerator prepared in Comparative Examples 1 to 4; it can be seen from the figure that after loading polydopamine and carbon nanotubes, the electrical output performance of the sample is significantly improved, the open circuit voltage increases from 19.36V of natural wood (Comparative Example 2) to 54.83V (Comparative Example 4), and the short circuit current increases from 0.14μA (Comparative Example 2) to 0.6μA (Comparative Example 4); after compression treatment, the output performance is further significantly improved, the open circuit voltage increases to 98.12V (Comparative Example 1), and the short circuit current increases to 1.1μA (Comparative Example 1); this phenomenon can be attributed to the following points. First, the abundant amino groups in polydopamine have a strong electron donating ability; secondly, the addition of carbon nanotubes greatly improves the conductivity of the sample, thereby accelerating electron transmission; at the same time, the compression treatment makes the sample surface smooth from rough, greatly increases the effective contact area, and thus significantly improves the output performance.
[0094] Figure 7 The ultra-depth-of-field microscope images of the carbon nanotube-loaded wood prepared in step 1③ of Example 1 and the compressed carbon nanotube-modified wood prepared in step 1④ are shown; as can be seen from the image, after the compression treatment, the surface of the sample changes from being rough and warped to being flat, the roughness at the micron level is reduced, and the surface roughness decreases from 11.79μm before compression to 9.52μm, reducing the adverse effects of tip contact on it during subsequent work.
[0095] Figure 8 The actual pictures are of the carbon nanotube-loaded wood prepared in step 1③ of Example 1 and the compressed carbon nanotube-modified wood prepared in step 1④; as can be seen from the figure, after the compression treatment, the surface of the sample changes from rough and warped to flat, and the thickness is reduced from 1.11mm to 0.65mm, which speeds up the electron transmission speed and thus improves the output performance.
[0096] Fig. 9 This is the SEM image of the compressed carbon nanotube-modified wood prepared in step 1④ of Example 1, Comparative Examples 5 and 6; it can be seen from the figure that the coating of polydopamine and carbon nanotubes is evenly distributed on each section, which proves that the modification method is applicable to wood with different sections.
[0097] Under the condition of a humidity environment of 20% RH, the wood-based friction nanogenerators prepared in Comparative Examples 1 to 4 were subjected to contact separation power generation tests with a pressure of 100 N and a frequency of 1 Hz. Fig.10The output performance diagram of the friction nanogenerators prepared with wood of different sections in Comparative Examples 1, 5 and 6; it can be seen from the figure that the friction nanogenerator assembled with the friction material prepared with the tangential section wood has the best output performance, with an open circuit voltage of 98.12V and a short circuit voltage of 1.1μA. The open circuit voltage of the friction nanogenerator assembled with the friction material prepared with the radial section wood is 77.71V, and the short circuit voltage is 0.85μA. The open circuit voltage of the friction nanogenerator assembled with the friction material prepared with the cross section wood is 86.05V, and the short circuit voltage is 1.03μA.
Claims
1. A method for preparing a high-humidity resistant wood-based friction nanogenerator, characterized in that It is carried out in the following steps:
1. Preparation of friction materials: ① Dissolve dopamine hydrochloride in Tris solution and disperse evenly to obtain a modified solution; ② Immersing the delignified wood in a modification solution and then drying it to obtain polydopamine-modified wood; ③ Place the polydopamine-modified wood in the carbon nanotube dispersion, apply vacuum pressure until the wood is completely immersed and maintained, then dry, repeat the immersion and drying multiple times until the wood turns black, and obtain the carbon nanotube-loaded wood; ④ compressing the carbon nanotube-loaded wood to obtain compressed carbon nanotube-modified wood; 2. Preparation of electrode materials: The natural wood chips are compressed to obtain veneers, and then the veneers are carbonized to obtain carbonized wood veneers; 3. Assembly of wood-based friction nanogenerator: ① Using compressed carbon nanotube-modified wood as the positive friction material and carbonized wood veneer as the positive electrode material, and then assembling them to obtain the positive electrode material of the friction nanogenerator; ② Using polytetrafluoroethylene film as negative friction material and copper foil as negative electrode material, and then assembling them to obtain the negative electrode material of the friction nanogenerator; ③ Assemble the positive electrode material of the friction nanogenerator and the negative electrode material of the friction nanogenerator to obtain a high-humidity resistant wood-based friction nanogenerator.
2. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The concentration of dopamine hydrochloride in the modified solution described in step 1① is 0.5mg / mL~2mg / mL; the concentration of the Tris solution described in step 1① is 5mmol / L~15mmol / L, and the pH is 8~8.
5.
3. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The delignified wood described in step 1② is specifically prepared according to the following steps: glacial acetic acid is added dropwise to a 1% to 3% by mass NaClO2 aqueous solution until the pH is 4 to 6 to obtain an impregnation solution, the wood is immersed in the impregnation solution, and the temperature is kept at 80°C to 100°C for 8h to 24h, and the impregnation solution is replaced every 6h to 8h during the insulation process until the wood turns white, and then washed with deionized water, and finally freeze-dried at a temperature of -80°C to -60°C for 12h to 24h to obtain delignified wood.
4. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 3, characterized in that The wood is basswood slices in cross section, radial section or tangential section, with a thickness of 1mm to 1.5mm.
5. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The volume ratio of the delignified wood and the modified liquid described in step 1② is 1cm 3 : (100-300) mL; the volume ratio of the polydopamine-modified wood and the carbon nanotube dispersion described in step 1 ③ is 1 cm 3 :(100~300)mL.
6. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The carbon nanotubes in the carbon nanotube dispersion described in step 1③ are hydroxylated multi-walled carbon nanotubes with a diameter of 5nm to 15nm and a length of 2μm to 8μm; the concentration of the carbon nanotube dispersion described in step 1③ is 0.5mg / mL to 2mg / mL.
7. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that In step 1②, the delignified wood is immersed in the modification liquid for 12 hours to 48 hours at room temperature; in step 1③, vacuum pressurization is applied at room temperature until the wood is completely immersed and maintained for 12 hours to 48 hours.
8. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The compression treatment described in step 1④ and step 2 is specifically carried out at room temperature and a pressure of 5MPa to 20MPa for 1h to 2h.
9. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The natural wood chips described in step 2 are natural basswood chips with a thickness of 0.5 mm to 1.5 mm.
10. The method for preparing a high-humidity resistant wood-based friction nanogenerator according to claim 1, characterized in that The carbonization treatment described in step 2 is specifically to heat the temperature to 700°C to 900°C at a heating rate of 2°C / min to 10°C / min under a nitrogen atmosphere, and then to perform the carbonization treatment for 1h to 2h under the conditions of a nitrogen atmosphere and a temperature of 700°C to 900°C.
Citation Information
Cited By
Cement-based friction nanogenerator and preparation method and application thereof
CN122969408A